Post-Traumatic Headache: Is It A Danger? - Restu Susanti (Health and Medical Journal, 2021)
Post-Traumatic Headache (PTH), is the most frequent complaint after Traumatic Brain Injury (TBI). PTH affects the quality of life of the sufferer. Post-traumatic headache is defined as secondary headache within 7 days after head trauma or after regained consciousness after head trauma. PTH's definitive mechanisms are still unknown, but hypotheses can be brought from clinical findings and diagnostic tests that have been conducted. PTH can originate from peripheral or central. A multidisciplinary approach is emphasized in the treatment of PTH due to the many associated symptoms